A Bibliometric Analysis of the Relationship Between Leadership Styles and Teacher Satisfaction in Education Management Research - Mislan Sihite; Asri Widiatsih; Loso Judijanto; Noor Fazariah Handayani (Eastasouth Institute, 2023)
This research employs bibliometric analysis and keyword occurrence assessment to explore the intricate relationship between leadership style and teacher satisfaction within the realm of educational management research. The analysis encompasses influential documents, thematic clusters, and prevalent keywords, providing a comprehensive overview of the current state of the literature. Noteworthy findings include the identification of top-cited documents, the delineation of thematic clusters addressing diverse aspects of educational management, and a focus on keywords such as